2022
DOI: 10.3389/fenvs.2022.887040
|View full text |Cite
|
Sign up to set email alerts
|

Water Conservation Ecological Service Function and Its Value Response Mechanism in a Nested Water Conservancy Project Area

Abstract: The Three Gorges Project is the largest water conservancy project in the world. To cope with the ecological problems of the subsidence zone in the Three Gorges Reservoir area, the Kaizhou water-level-regulating dam was built, forming a model of nested water conservancy projects. The Pengxi River Basin is affected not only by this project but also by human activities in the reservoir area and changes in the substratum and hydro-meteorology, which exert influences on the water connotation function and its ecolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…However, demands for the protection of water resources and ecological environments restrict development (Bian et al, 2022; Jiang et al, 2022). The interference of human activities on the ecological environments has been gradually amplified (Zeng et al, 2022; Zhu et al, 2017). Water conservancy projects are essential for flood control, water storage, sediment retention and enhancement of agricultural production.…”
Section: Introductionmentioning
confidence: 99%
“…However, demands for the protection of water resources and ecological environments restrict development (Bian et al, 2022; Jiang et al, 2022). The interference of human activities on the ecological environments has been gradually amplified (Zeng et al, 2022; Zhu et al, 2017). Water conservancy projects are essential for flood control, water storage, sediment retention and enhancement of agricultural production.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have confirmed the feasibility of ecological operation, but most of the current ecological operations have the characteristic of "high-flow-rate discharge in the flood period" (Lan et al, 2022). With the increase in ecological protection awareness, the fulfillment of ecological demand at a high level has become an important goal (Niu et al, 2021), and ecological operation has expanded from the guarantee of ecological base flow of a single section to considering the ecological water demand of the area downstream (Tsai et al, 2015;Zeng et al, 2022). Because different rivers have different hydrological, water-sediment, and hydroecological characteristics that are affected by the operation and storage capacity of the reservoir itself, an obvious antagonistic effect exists between the benefit and ecological objectives.…”
Section: Introductionmentioning
confidence: 99%